2010
DOI: 10.1007/s10526-010-9301-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intercropping with aromatic plants on the diversity and structure of an arthropod community in a pear orchard

Abstract: Five aromatic plants, Centaurea cyanus, Saturela hortensis, Nepeta cataria, Agerarum houstonianum, and Ocimum basilicum, were assessed as intercrops in a pear orchard, and all significantly reduced the pest population compared with that in the plot natural grasses. The decrease was particularly marked for C. cyanus, S. hortensis, and A. houstonianum, and plots intercropped with these aromatic plants also had significantly higher values of ratios of natural enemies to pests, Simpson's index, the Shannon-Wiener … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 27 publications
(17 reference statements)
1
38
0
4
Order By: Relevance
“…Geranium oil has diverse effects on the behavior of arthropods, with effects on Amblyomma americanum (L.) (Tabanca et al., ), B. tabaci (Yarahmadi et al., ), and mosquitoes (Ali et al., ). In general, essential oils contain VOCs from aromatic plants, which are unattractive and repellent to certain insect species (Basedow et al., ; Song et al., , ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geranium oil has diverse effects on the behavior of arthropods, with effects on Amblyomma americanum (L.) (Tabanca et al., ), B. tabaci (Yarahmadi et al., ), and mosquitoes (Ali et al., ). In general, essential oils contain VOCs from aromatic plants, which are unattractive and repellent to certain insect species (Basedow et al., ; Song et al., , ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Geranium oil has diverse effects on the behavior of arthropods, with effects on Amblyomma americanum (L.) (Tabanca et al, 2013), B. tabaci (Yarahmadi et al, 2013), and mosquitoes (Ali et al, 2013). In general, essential oils contain VOCs from aromatic plants, which are unattractive and repellent to certain insect species (Basedow et al, 2006;Song et al, 2010Song et al, , 2011. Zhang et al (2013Zhang et al ( ,b, 2014a reported that the volatiles of aromatic plants repelled two tea pests, Ectropis obliqua (Prout) and E. vitis.…”
Section: Discussionmentioning
confidence: 99%
“…In their research on dicotyledonous weeds, Wilson & Aebisher (1995) reported that the density of most arthropod species decreased significantly as distance from crop edge increased from 0 to 128 m. Some authors (Winkler, 2005;Bàrberi et al, 2010) have reviewed the importance of vegetation diversity for enhancing populations of beneficial arthropods in cropland. Wyss (1996), Simon et al (2010) and Song et al (2010) reported a positive effect of plant comunity diversification on beneficial arthropods in orchards. Non-crop habitats bordering agricultural fields in Europe have been found to have a favourable effect on a number of beneficials as spiders, ladybugs, and syrphids (Hillocks, 1998;Ernoult et al, 2013).…”
Section: Plant Comunitiesmentioning
confidence: 98%
“…Aromatic plants are a special type of plant group as they have both medicinal and aromatic properties and they contain a variety of volatile oils that are well known for their insecticidal, antifeedant, and repellent effects on insect pests (Song et al 2010). In recent years, intercropping with aromatic plants as an alternative method for reducing browsing pressure has attracted research attention.…”
mentioning
confidence: 99%